The effect of resistance and plyometric training methods with concentration on ability mawashi geri men's junior karate athlete dojo tako simalungun district - Muhammad Prawibowo; Alnedral Alnedral; Hendri Neldi; Ahmad Chaeroni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Karate athletes must master mawashi geri. To maximize athlete performance, Resistance and Plyometric Training Methods must be used. This study examines how resistance and plyometric training affect Mawashi Geri's proficiency. Simalungun junior karate practitioner Putera Dojo Tako. A 2x2 factorial experimental design is used in this investigation. The study included 32 Simalungun-based junior karate athletes from Putera Dojo Tako. Grid concentration and mawashi geri kicking proficiency tests were used. Two-way ANOVA and the Tukey test were used to analyze the data. The research shows that resistance and plyometric training improve karate contestants' mawasahi geri kicks. Next, strength training and plyometric training affect karate athletes' mawasahi geri kick performance. At Dojo Tako in Simalungun, male junior karate participants' mawasahi geri kicks varied, especially when performed with attention and passion. Male junior karate athletes at Dojo Tako, Simalungun Regency, who received resistance and low-intensity plyometric training showed variances in mawasahi geri kicking proficiency